Is There a Relationship between Information and Communication Technologies Infrastructure, Electricity Consumption and Total Factor Productivity? Evidence from a Panel of African Countries - Nondo, Chali (International Journal of Energy Economics and Policy, 2018)
This study examines the short-run and long-run relationships among ICT, electricity consumption, and total factor productivity (TFP) growth for a panel of 26 African countries. The long-run relationship is determined using the three standard panel causality tests. As a whole, empirical results provide clear evidence that ICT, electricity consumption and TFP have a long run equilibrium relationship. However, results also show lots of variation on the impact of electricity consumption and ICT access on TFP. Panel estimations reveal that electricity consumption has a statistically positive impact on TFP growth in 22 countries, but has a negative effect in four countries. Similarly, the sign of the effect of ICT on TFP growth varies across countries, being positive in some and negative in others. Additional insights from the empirical estimations show presence of a two-way causality between electricity consumption and TFP and a unidirectional causality running from ICT to TFP. Overall, results suggest that bridging the infrastructure gap is a vital step for African countries to take towards sustaining economic growth. Keywords: ICT; Electricity consumption; Total factor productivity; Panel Granger Causality JEL Classifications: C14, C32; O3; Q4